High Expression of miR-204 in Chicken Atrophic Ovaries Promotes Granulosa Cell Apoptosis and Inhibits Autophagy - Cui, Zhifu; Liu, Lingbin; Kwame Amevor, Felix; Zhu, Qing; Wang, Yan; Li, Diyan; Shu, Gang; Tian, Yaofu; Zhao, Xiaoling (Frontiers in Cell and Developmental Biology, 2020)
Chicken atrophic ovaries have decreased volume and are indicative of ovarian failure, presence of a tumor, or interrupted ovarian blood supply. Ovarian tumor is accompanied by an increase in follicular atresia, granulosa cell (GC) apoptosis, and autophagy. In a previous study, we found using high throughput sequencing that miR-204 is highly expressed in chicken atrophic ovaries. Thus, in the present study, we further investigated its function in GC apoptosis and autophagy. We found that overexpression of miR-204 reduced mRNA and protein levels of proliferation-related genes and increased apoptosis-related genes. Cell counting kit-8 (CCK-8), 5-ethynyl-2-deoxyuridine (EdU), and flow cytometry assays revealed that miR-204 inhibited GC proliferation and promoted apoptosis. Furthermore, we confirmed with reporter gene assays that Forkhead box K2 (FOXK2) was directly targeted by miR-204. FOXK2, as a downstream regulator of phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signal pathways, promoted GC proliferation and inhibited apoptosis. Subsequently, we observed that miR-204 was involved in GC autophagy by targeting Transient Receptor Potential Melastatin 3 (TRPM3). The luciferase activities of the two binding sites of TRPM3 were decreased in response to treatment with a miR-204 mimic, and the autophagic flux was increased after miR-204 inhibition. However, overexpression of miR-204 had opposite results in autophagosomes and autolysosomes. miR-204 inhibits GC autophagy by suppressing the protein expression of TRPM3/AMP-activated protein kinase (AMPK)/ULK signaling pathway components. Inhibition of miR-204 enhanced autophagy by accumulating and degrading the protein levels of LC3-II (Microtubule Associated Protein Light Chain 3B) and p62 (Protein of 62 kDa), respectively, whereas miR-204 overexpression was associated with contrary results. Immunofluorescence staining showed that there was a significant reduction in the fluorescent intensity of LC3B, whereas p62 protein was increased after TRPM3 silencing. Collectively, our results indicate that miR-204 is highly expressed in chicken atrophic ovaries, which promotes GC apoptosis via repressing FOXK2 through the PI3K/AKT/mTOR pathway and inhibits autophagy by impeding the TRPM3/AMPK/ULK pathway.